The Employment Multiplier in an Expanding Industrial Market: Los Angeles County, 1940-47 - Hildebrand, George H.; Mace, Arthur (The Review of Economics and Statistics, 1950)
George H. Hildebrand, Arthur Mace, The Employment Multiplier in an Expanding Industrial Market: Los Angeles County, 1940-47, The Review of Economics and Statistics, Vol. 32, No. 3 (Aug., 1950), pp. 241-249